Investigation of effect of various hot gas atomisation and melting pot temperatures on tin alloy powder product - Basyir, Abdul; Kurnia, Robby; Cherly Firdharini,; Aryanto, Didik; Widayatno, Wahyu Bambang; Wismogroho, Agus Sukarto (Penerbit Universiti Kebangsaan Malaysia, 2022)
This research investigates the effect of different types of hot gas atomisation (argon, nitrogen and oxygen) and melting pot temperatures on the particle size distribution, microstructure, density and phase of tin alloy (Sn-Cu-Ni-Ge) powder products. The tin alloy powder produced by hot argon gas atomisation had the greatest density (7.84 g/cm3 ) and the most spherical shape. While the tin alloy powder generated by hot oxygen gas atomisation had the lowest density (6.83 g/cm3 ), the highest endothermic area (60.41695 area unit) and the most elongated, irregular shape. Hot argon and nitrogen gas atomisation at a melting pot temperature of 800 °C produced a higher yield of 0-25 µm powder than at 700 °C. By contrast, hot oxygen atomisation produced the opposite result. However, all the powder products prepared at 800 °C had a higher spherical shape ratio in the range of 0-25 µm. Tin alloy powder produced by hot oxygen gas atomisation comprised only the elements of Sn and Cu, while the powder generated by hot argon and nitrogen gas atomisation consisted of elements such as the ingot of this powder.